2016
DOI: 10.5194/bg-13-817-2016
|View full text |Cite
|
Sign up to set email alerts
|

Soluble trace metals in aerosols over the tropical south-east Pacific offshore of Peru

Abstract: Abstract. Bulk aerosol samples collected during cruise M91 of FS Meteor off the coast of Peru in December 2012 were analysed for their soluble trace metal (Fe, Al, Mn, Ti, Zn, V, Ni, Cu, Co, Cd, Pb, Th) and major ion (including NO − 3 and NH + 4 ) content. These data are among the first recorded for trace metals in this relatively poorly studied region of the global marine atmosphere. To the north of ∼ 13 • S, the concentrations of several elements (Fe, Ti, Zn, V, Ni, Pb) appear to be related to distance from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…This approach has been used to provide a global model of atmospheric copper inputs to the ocean [63] which does illustrate that for this trace element both anthropogenic and dust sources are important, consistent with an observed average enrichment of copper globally [64]. In general, anthropogenic trace element emissions will be from highly populated and industrialized regions and hence the deposition patterns for such emissions is likely to be more similar to that of nitrogen than dust, but there are additional important source regions for some trace elements associated with regions of major mining and smelting activity, such as in the coastal regions of Peru and northern Chile [65]. Figure 5 shows the distribution of some trace elements sampled along the track of the D361 cruise and the average concentrations in different air masses are reported in table 4.…”
Section: Atmospheric Deposition Of Other Trace Elementsmentioning
confidence: 58%
“…This approach has been used to provide a global model of atmospheric copper inputs to the ocean [63] which does illustrate that for this trace element both anthropogenic and dust sources are important, consistent with an observed average enrichment of copper globally [64]. In general, anthropogenic trace element emissions will be from highly populated and industrialized regions and hence the deposition patterns for such emissions is likely to be more similar to that of nitrogen than dust, but there are additional important source regions for some trace elements associated with regions of major mining and smelting activity, such as in the coastal regions of Peru and northern Chile [65]. Figure 5 shows the distribution of some trace elements sampled along the track of the D361 cruise and the average concentrations in different air masses are reported in table 4.…”
Section: Atmospheric Deposition Of Other Trace Elementsmentioning
confidence: 58%
“…Therefore, the availability of reduced carbon compounds may essentially control N 2 fixation in mode water eddies. Assuming that organic-matter export is limiting for N loss as previously suggested (Babbin et al, 2014;Ogawa et al, 2001;Bianchi et al, 2014) and that deep-water N 2 fixation is a non-cyanobacterial (i.e., heterotrophic) process as shown by the diversity of the diazotrophs and the stimulation of N 2 fixation rates after glucose addition, the interplay between both may be even closer than previously thought.…”
Section: Patterns Of N 2 and C Fixation In The Three Eddiesmentioning
confidence: 70%
“…Several studies have highlighted the importance of atmospheric Fe supply to the ETNA (Voss et al, 2004; as a major factor of primary production. However, a comparable atmospheric Fe source is missing in the ETSP (Baker et al, 2016). Previous studies (Scholz et al, 2014) have identified the ETSP Fe supply as benthic; however, the question of how much Fe is transported from the sediments to the sea surface has not yet been fully clarified.…”
Section: The Impact Of Changing N : P Ratios As a Results Of Ocean Deomentioning
confidence: 98%